Children and childhood: a social category in debate - Eloisa Acires Candal Rocha (Universidade Federal de Santa Catarina, 2004)
The definition of childhood has been given mainly by a cut defined age as opposed to adults, the lack of age, the immaturity or the inadequate social integration. This view was contested mainly at the end of the twentieth century when it outlined a concept of childhood, a new tenant that is time to consider the different ways of entering the child in reality, the adult world, in daily activities in play and in different forms of cultural expression. However, as we shall see, the child remains on the horizon, as depository of the hopes of the future society, one way or another, for the preservation and disciplinação.